Bruteforce Attacks Blocking Solution on Embedded SIP Communication Server - Rezac, Filip; Safarik, Jakub; Voznak, Miroslav; Rozhon, Jan; Tomala, Karel; Vychodil, Jiri (Communications - Scientific letters of the University of Zilina, 2013)
This article deals with embedded SIP communication server with an easy integration into the computer network based on open source solutions and its effective defense against the most frequent attack in the present – Denial of Service. The article contains brief introduction into the Bright Embedded Solution for IP Telephony – BESIP and describes the most common types of DoS attacks, which are applied on SIP elements of the VoIP infrastructure including the results of defensive mechanism that has been designed.